(−)-Epigallocatechin-3-gallate mitigates cyclophosphamide-induced intestinal injury by modulating the tight junctions, inflammation and dysbiosis in mice. Issue 22 (3rd November 2021) - Wei, Ran; Liu, Xingquan; Wang, Yuefei; Dong, Junjie; Wu, Fenghua; Mackenzie, Gerardo G.; Su, Zhucheng
Abstract : Schematic diagram depicting the main mechanisms of EGCG for mitigating cyclophosphamide (CTX)-induced intestinal injury. Abstract : Cyclophosphamide (CTX) is an antitumor drug commonly used to treat various cancer types. Unfortunately, its toxic side effects, including gastrointestinal (GI) toxicity, affect treatment compliance and patients' prognosis. Thus, there is a critical need of evaluating strategies that may improve the associated GI toxicity induced by CTX. In this work, we evaluated the capacity of epigallocatechin-3-gallate (EGCG), a major constituent of green tea, to improve the recovery of gut injury induced by CTX in mice. Treatment with CTX for 5 days severely damaged the intestinal structure, increased immune-related cytokines (TNFα, IL-10 and IL-21), reduced the expression levels of tight junction proteins (ZO-1, occludin, claudin-1), induced reactive oxygen species, altered the composition of gut microbiota, and reduced short chain fatty acid levels. EGCG treatment, starting one day after the last CTX dose, significantly improved the intestinal structure, ameliorated gut permeability, and restored ZO-1, occludin and claudin-1 levels. Moreover, EGCG reduced TNFα, IL-10 and IL-21 levels and decreased oxidative stress by regulating the activities of the antioxidant enzymes catalase, superoxide dismutase and glutathione peroxidase. Finally, EGCG treatment restored the composition of gut microbiota and the levels of the short chain fatty acids. In conclusion, these findings indicate that EGCG may function as an effective bioactive compound to minimize CTX-induced GI tract toxicity.